Inhibitory effect of Selaginella doederleinii hieron on human cytochrome P450 - Lin, Fei; Lin, Xinhua; Wang, Xuewen; Mei, Guanghui; Chen, Bing; Yao, Hong; Huang, Lingyi (Frontiers in Pharmacology, 2023)
Selaginella doederleinii Hieron is a traditional Chinese herbal medicine, the ethyl acetate extract from S. doederleinii (SDEA extract) showed favorable anti-cancer potentials. However, the effect of SDEA on human cytochrome P450 enzymes (CYP450) remains unclear. To predict the herb-drug interaction (HDI) and lay the groundwork for further clinical trials, the inhibitory effect of SDEA and its four constituents (Amentoflavone, Palmatine, Apigenin, Delicaflavone) on seven CYP450 isoforms were investigated by using the established CYP450 cocktail assay based on LC-MS/MS. SDEA showed strong inhibitory effect on CYP2C9 and CYP2C8 (IC50≈1 μg/ml), moderate inhibitory effect against CYP2C19, CYP2E1 and CYP3A (IC50 < 10 μg/ml). Among the four constituents, Amentoflavone had the highest content in the extract (13.65 %) and strongest inhibitory effect (IC50 < 5 μM), especially for CYP2C9, CYP2C8 and CYP3A. Amentoflavone also showed time-dependent inhibition on 2C19 and 2D6. Apigenin and Palmatine both showed concentration-dependent inhibition. Apigenin inhibited CYP1A2, CYP2C8, CYP2C9, CYP2E1 and CYP3A4. Palmatine inhibited CYP3A4 and had a weak inhibitory effect on CYP2E1. As for Delicaflavone, which has the potential to develop as an anti-cancer agent, showed no obvious inhibitory effect on CYP450 enzymes. To sum up, Amentoflavone may be one of the main reasons for the inhibition of SDEA on CYPs, the potential HDI should be considered when SDEA or Amentoflavone were used with other clinical drugs. On the contrast, Delicaflavone is more suitable to develop as a drug for clinical use, considering the low level of CYP450 metabolic inhibition.